Experimental SARS-CoV-2 Infection of Elk and Mule Deer - Stephanie M. Porter; Airn E. Hartwig; Helle Bielefeldt-Ohmann; Jeffrey M. Marano; J. Jeffrey Root; Angela M. Bosco-Lauth (Emerging Infectious Diseases, 2024)
To assess the susceptibility of elk (Cervus canadensis) and mule deer (Odocoileus hemionus) to SARS-CoV-2, we performed experimental infections in both species. Elk did not shed infectious virus but mounted low-level serologic responses. Mule deer shed and transmitted virus and mounted pronounced serologic responses and thus could play a role in SARS-CoV-2 epidemiology.